The role of mesenchymal stem cell-derived EVs in diabetic wound healing - Jiang, Min; Jiang, Xupin; Li, Hongmei; Zhang, Can; Zhang, Ze; Wu, Chao; Zhang, Junhui; Hu, Jiongyu; Zhang, Jiaping (Frontiers in Immunology, 2023)
Diabetic foot is one of the most common complications of diabetes, requiring repeated surgical interventions and leading to amputation. In the absence of effective drugs, new treatments need to be explored. Previous studies have found that stem cell transplantation can promote the healing of chronic diabetic wounds. However, safety issues have limited the clinical application of this technique. Recently, the performance of mesenchymal stem cells after transplantation has been increasingly attributed to their production of exocrine functional derivatives such as extracellular vesicles (EVs), cytokines, and cell-conditioned media. Evs contain a variety of cellular molecules, including RNA, DNA and proteins, which facilitate the exchange of information between cells. Evs have several advantages over parental stem cells, including a high safety profile, no immune response, fewer ethical concerns, and a reduced likelihood of embolism formation and carcinogenesis. In this paper, we summarize the current knowledge of mesenchymal stem cell-derived EVs in regulating angiogenesis and accelerating diabetic wound healing, as well as their potential clinic applications.